ANTECEDENTS OF SECOND-HAND CLOTHES PURCHASE INTENTION AT THRIFT STORES - Wijayanti, Cynthia Anna; Siahaan, Juniarty; Sembel, Jacquelinda Sandra (Faculty of Economics and Business Universitas Pelita Harapan, 2024)
Several previous research studies have explored purchase intentions for second-hand items like mobile phones, automobiles, and other products; however, the need for more literature explicitly focusing on the apparel industry and second-hand clothing is still open. Various factors motivating consumers to purchase second-hand clothes have been quantitatively studied, including economic, ecological, fashion, recreational, and ideological motivations. However, there is a need for a comprehensive quantitative study that examines the factors that influence the bargain-hunting motives and antecedents of purchase intentions to buy second-hand clothing at thrift stores. This study used a modified model to know the factors that affect the purchase decisions of second-hand clothes at thrift stores in Indonesia. The study involved 108 respondents of second-hand clothing buyers and was analyzed using Structural Equation Modeling with the software Smart PLS. The result showed that five hypotheses are supported, and seven are not supported. Frugality and Trust influenced bargain-hunting motives (Economic Motivations), while eco-consciousness, Trust, and bargain-hunting reasons also influenced the intention to purchase second-hand clothes. Regardless of the remaining seven hypotheses that were not supported, the research gives implications for managerial suggestions, limitations, and future research recommendations.